COST CONSEQUENCE ANALYSIS OF DIABETIC NEPHROPATHY MANAGEMENT IN A TERTIARY CARE HOSPITAL - KURIEN, SARA; R, MANOHAR V; KUMAR K, SHARATH; RAVINDRAN, ARUN (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: The objective of the study was to assess the overall costs incurred to patients with diabetic nephropathy (DN) and to disclose the elements that could affect them. Methods: Two-year retrospective, observational study using hospital database of a tertiary care center in Mangalore. Outcomes were assessed based on the survival of patients, length of hospital stay, coexistence of risk factors, and comorbidities. Severity was identified through staging of the disease; costs and clinical outcomes assessed through the cost consequence analysis. Results: Of the 156 patients who met the diagnostic criteria, it was noticed that demographic age factor for DN was declining and the minimum duration to develop DN was seen to be as less as 1–5 years. In spite of having ample evidence that angiotensin-converting enzyme inhibitors (ACEIs) and angiotensin receptor blockers (ARBs) control the progression of disease, not many doctors were inclined to follow. A study showed that patients of DN with chronic kidney disease (CKD) spent more and patients with CKD and end-stage renal disease (ESRD) spent double than those with CKD alone. Conclusion: Overall costs in treating 156 patients of DN amounted to 10 lakh INR and the major determinant was the cost of investigations, unlike what was expected of the drug prices.